Effectiveness of the Boston University Approach to Psychiatric Rehabilitation in Improving Social Participation in People With Severe Mental Illnesses: A Randomized Controlled Trial - Sanches, Sarita A.; Swildens, Wilma E.; Schaefer, Barbara; Moerbeek, Mirjam; Feenstra, Talitha L.; van Asselt, Antoinette D. I.; Danner, Unna N.; van Weeghel, Jaap; van Busschbach, Jooske T. (Frontiers in Psychiatry, 2020)
Background People with severe mental illnesses (SMIs) have difficulty participating in society through work or other daily activities. Aims To establish the effectiveness with which the Boston University Approach to Psychiatric Rehabilitation (BPR) improves the level of social participation in people with SMIs. Method In a randomized controlled trial involving 188 people with SMIs, we compared BPR (n=98) with an Active Control Condition (ACC, n=90) (Trial registration ISRCTN88987322). Multilevel modeling was used to study intervention effects over two six-month periods. The primary outcome measure was level of social participation, expressed as having participated in paid or unpaid employment over the past six months, as the total hours spent in paid or unpaid employment, and as the current level of social participation. Secondary outcome measures were clients’ views on rehabilitation goal attainment, Quality of Life (QOL), personal recovery, self-efficacy and psychosocial functioning. Results During the study, social participation, QOL and psychosocial functioning improved in patients in both groups. However, BPR was not more effective than ACC on any of the outcomes. Better social participation was predicted by previous work experience and a lower intensity of psychiatric symptoms. Conclusions While ACC was as effective as BPR in improving the social participation of individuals with SMIs, much higher percentages of participants in our sample found (paid) work or other meaningful activities than in observational studies without specific support for social participation. This suggests that focused rehabilitation efforts are beneficial, irrespective of the specific methodology used.